The invisible boy - Ludwig, Trudy; Barton, Patrice, 1955- (New York : Alfred A. Knopf, 2013)
Brian has always felt invisible at school, but when a new student, Justin, arrives, everything changes.
Includes bibliographical references.
A Junior Library Guild selection
Keywords: Popularity -- Fiction; Friendship -- Fiction; Schools -- Fiction; Popularity -- Juvenile fiction; Friendship -- Juvenile fiction; Schools -- Juvenile fiction